Genome Sequence of a Genotype 2 Hepatitis E Virus World Health Organization Reference Strain - Kaiser, Marco (Genome Announc, 2017)
We report here the sequence of a genotype 2a reference strain of hepatitis E virus (HEV), developed on behalf of the World Health Organization. The HEV reference strain is intended for use in assays based on nucleic acid amplification for the validation of HEV RNA detection.